2005
DOI: 10.1039/b504149j
|View full text |Cite
|
Sign up to set email alerts
|

The stereocontrolled total synthesis of altohyrtin A/spongistatin 1: the southern hemisphere EF segment

Abstract: The fully functionalised C29-C51 southern hemisphere of altohyrtin A/spongistatin 1 , incorporating the E- and F-ring tetrahydropyran rings and the unsaturated side chain, has been synthesised in a highly convergent and stereocontrolled manner. Key steps in the synthesis of this phosphonium salt include four highly diastereoselective, substrate-controlled, boron aldol reactions to establish key C-C bonds and accompanying stereocentres, where the introduction of the chlorodiene side chain and the C47 hydroxyl-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 77 publications
2
13
0
1
Order By: Relevance
“…(162) (163) Tebbe's reagent was used to transform esters to alkenyl ethers in synthetic approaches to integramycin [224], ␣-(1-6)-Cdisaccharides [893] and C-glycolyl amino acids [894]. Petasis reagent, Cp 2 TiMe 2 , was used to methylenate esters, lactones, or ketones in synthesis of mycalamide A [853], dihydropyrrins [492], toward vinigrol [895], (+)-phorboxazole A [70] and spongistatin 1 [896]. Petasis reagent was also used to methylenate unsymmetrical oxalates [897] and acetamides [898].…”
Section: Formation Of Carbon-carbon and -Nitrogen Bonds From Carbonylmentioning
confidence: 99%
“…(162) (163) Tebbe's reagent was used to transform esters to alkenyl ethers in synthetic approaches to integramycin [224], ␣-(1-6)-Cdisaccharides [893] and C-glycolyl amino acids [894]. Petasis reagent, Cp 2 TiMe 2 , was used to methylenate esters, lactones, or ketones in synthesis of mycalamide A [853], dihydropyrrins [492], toward vinigrol [895], (+)-phorboxazole A [70] and spongistatin 1 [896]. Petasis reagent was also used to methylenate unsymmetrical oxalates [897] and acetamides [898].…”
Section: Formation Of Carbon-carbon and -Nitrogen Bonds From Carbonylmentioning
confidence: 99%
“…As reações aldólicas com dupla e tripla estereodiferenciação foram descritas por Paterson e colaboradores nos estudos visando a síntese do macrolídeo espongistatina 1 (altoirtina A) [36][37][38][39][40] . Na sín-tese da subunidade espiroacetal-AB, os autores exploraram combinações quirais diferentes entre β-alcóxi-aldeídos, β-alcóxi-metilcetonas e boranas aquirais e quirais (Esquema 10) 36,37 .…”
Section: Reações Aldólicas Com Estereoindução 15-antiunclassified
“…Initial NMR experiments in CD 2 Cl 2 indicated that the previously employed Lewis acid Chx 2 BCl did not efficiently generate the desired enol-boronate. Consequently, the more reactive Lewis acid, Chx 2 BBr, 74 was employed. Moderate diastereoselectivity (β:α = 3:1) was obtained using a slight excess of the Lewis acid (1.25 equiv), albeit at the expense of yield (33%, Scheme 27).…”
Section: Resultsmentioning
confidence: 99%